2007
DOI: 10.1086/521328
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Galaxy Formation on Thermodynamics of the Intracluster Medium

Abstract: We present detailed comparisons of the intracluster medium (ICM) in cosmological Eulerian cluster simulations with deep Chandra observations of nearby relaxed clusters. To assess the impact of galaxy formation, we compare two sets of simulations, one performed in the nonradiative regime and another with radiative cooling and several physical processes critical to various aspects of galaxy formation: star formation, metal enrichment, and stellar feedback. We show that the observed ICM properties outside cluster… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

79
858
6
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 669 publications
(944 citation statements)
references
References 93 publications
(199 reference statements)
79
858
6
1
Order By: Relevance
“…Our finding that the hydrostatic X-ray masses are larger than the weak lensing masses contradicts the results from many recent numerical simulations, all of which conclude that the hydrostatic assumption underestimates the true mass owing to its neglect of pressure support from gas bulk motions (e.g., Nagai et al 2007;Piffaretti & Valdarnini 2008;Meneghetti et al 2010). If the weak lensing mass is indeed unbiased (or less biased) and thus, on average, more representative of the true mass, then one would expect the weak lensing masses to be larger than the hydrostatic X-ray masses.…”
Section: The Mass Discrepancycontrasting
confidence: 91%
See 2 more Smart Citations
“…Our finding that the hydrostatic X-ray masses are larger than the weak lensing masses contradicts the results from many recent numerical simulations, all of which conclude that the hydrostatic assumption underestimates the true mass owing to its neglect of pressure support from gas bulk motions (e.g., Nagai et al 2007;Piffaretti & Valdarnini 2008;Meneghetti et al 2010). If the weak lensing mass is indeed unbiased (or less biased) and thus, on average, more representative of the true mass, then one would expect the weak lensing masses to be larger than the hydrostatic X-ray masses.…”
Section: The Mass Discrepancycontrasting
confidence: 91%
“…We then fitted the pressure profile of each cluster with the generalised Navarro, Frank & White (GNFW) model introduced by Nagai et al (2007), viz.,…”
Section: X-ray Pressure Profilementioning
confidence: 99%
See 1 more Smart Citation
“…This quantity reflects the total thermal energy of the ICM and is predicted to be a robust, low scatter mass proxy from simulations (e.g. Kravtsov et al 2006;Nagai et al 2007) which has recently been well confirmed by observations (e.g. Arnaud et al 2007;Vikhlinin et al 2009a;Arnaud et al 2010).…”
Section: Y Xmentioning
confidence: 58%
“…Inside this high-pressure tube, we model the pressure with a power-law function that depends only on the radial distance from the Coma centre: P tube (r) = P s (r/r s ) γ , where r is the radial distance, r s is a constant and P s and γ are the model parameters. This pressure tube is placed over a spherically symmetric generalized Navarro-Frenk-White (GNFW) pressure model (Nagai, Kravtsov & Vikhlinin 2007;Arnaud et al 2010) for the Coma cluster, which is constrained from the SZ-data excluding the radio relic wedge. We let the pressure excess terminate at the radio relic position (or any arbitrary position determined by the SZE data alone), beyond which the SZE signal is contributed only from the main cluster's GNFW pressure.…”
Section: Modelsmentioning
confidence: 99%